2020
DOI: 10.1016/j.purol.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

What to expect from a non-suspicious prostate MRI? A review

Abstract: Abbreviations mpMRI Multiparametric Magnetic Resonance Imaging NPV Negative Predictive Value Résumé Contexte : La réalisation d'une IRM multiparamétrique (IRMmp) est désormais recommandée avant la réalisation de biopsies prostatiques. En revanche, la conduite à tenir en présence d'une IRMmp non-suspecte (Score Likert ou PIRADS 1-2) est toujours débattue. Objectifs : Faire une synthèse de la littérature récente pour répondre à trois questions. 1) Faut-il réaliser des biopsies systématisées en présence d'une IRM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
(91 reference statements)
1
2
0
1
Order By: Relevance
“…At our medical center, 15.65% (216 eligible patients out of 1380 overall) between 2018 and 2020 showed negative mpMRI, from which 75% received prostate biopsy with only 5.1% of them showing clinically significant prostate cancer. Previous studies showed negative predictive values (NPV) of mpMRI, ranging from 76 to 99% [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Thus, the negative prognostic value of mpMRI at our institute is sufficient and congruent to other data.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…At our medical center, 15.65% (216 eligible patients out of 1380 overall) between 2018 and 2020 showed negative mpMRI, from which 75% received prostate biopsy with only 5.1% of them showing clinically significant prostate cancer. Previous studies showed negative predictive values (NPV) of mpMRI, ranging from 76 to 99% [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Thus, the negative prognostic value of mpMRI at our institute is sufficient and congruent to other data.…”
Section: Discussionsupporting
confidence: 86%
“…Clinical and laboratory factors such as family history, digital rectal examination, total PSA, PSA density, PSA velocity, Biomarkers (e.g., PCA3, PHI, 4Kscore) and BRCA mutation analysis can support the decision making progress regarding prostate cancer evaluation with prostate biopsy and help in the argumentation against overtreatment. Unfortunately, most of these factors are still being investigated and partly show incongruent data (in case of total PSA, age or prostate volume) [ 8 , 10 , 15 , 21 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although 20% refused biopsy control due to a normal MRI and a low and stable PSA, this has shown a high negative predictive value for discarding significant tumors. 1…”
mentioning
confidence: 99%
“…Su capacidad para distinguir la afectación extraprostática depende principalmente de su extensión (puntos de corte en <1 mm y >3 mm para ser capaz de detectar correctamente el 14% ó 100% de casos, respectivamente). De hecho, no se recomienda la realización de RMmp en pacientes de bajo riesgo únicamente con fines de estadificación local [57]. En cambio, cuando se emplea una RM de 3 Tesla o se añaden imágenes funcionales a las ponderadas en T2 aumentará notablemente la sensibilidad para identificar afectación extraprostática y de vesículas seminales.…”
Section: Histopatología De La Pieza De Prunclassified